2019
DOI: 10.1186/s12887-019-1544-1
|View full text |Cite
|
Sign up to set email alerts
|

Minoxidil versus placebo in the treatment of arterial wall hypertrophy in children with Williams Beuren Syndrome: a randomized controlled trial

Abstract: Background Insufficient elastin synthesis leads to vascular complications and arterial hypertension in children with Williams-Beuren syndrome. Restoring sufficient quantity of elastin should then result in prevention or inhibition of vascular malformations and improvement in arterial blood pressure. Methods The aim of this study was to assess the efficacy and safety of minoxidil on Intima Media Thickness (IMT) on the right common carotid artery after twelve-month treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…The mentioned studies agree on the possible side effects of minoxidil in paediatric population, hypertrichosis is the most common, and fluid retention, arrhythmia, electrocardiogram alterations and pericarditis are some of the most severe [ 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…The mentioned studies agree on the possible side effects of minoxidil in paediatric population, hypertrichosis is the most common, and fluid retention, arrhythmia, electrocardiogram alterations and pericarditis are some of the most severe [ 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 60%
“…However, there are reports of systemic toxicity in children due to percutaneous absorption of topical minoxidil [ 14 ]. Regarding oral minoxidil and children the current scientific evidence is limited to a report of the accidental ingestion of minoxidil [ 14 ], a randomized clinical trial with 9 patients receiving oral minoxidil treatment for arterial wall hypertrophy for Williams–Beuren syndrome [ 15 ], and some case series about the use of oral minoxidil for refractory hypertension in children [ 16 , 17 , 18 ]. In addition, a recently published systematic review [ 4 ] addressed the issue of minoxidil and children, finding only reports of topical minoxidil in children and one report of low-dose oral minoxidil in a 11-years-old female.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pharmacologic therapy has also shown promise. Several studies demonstrated that the antihypertensive medication minoxidil stimulates elastic fiber synthesis, improves the function of existing fibers, and decreases fiber degradation [108][109][110]. These synergistic effects are hypothesized to explain the reversal of age-related arterial changes reported in murine models 110.…”
mentioning
confidence: 99%